Perspektif Perilaku dalam Niat Adopsi Financial Technology: Peran Literasi Digital, Toleransi Risiko, dan Pengaruh Sosial - Susanti, Susanti; Nurtyastuti, Titis (JURNAL ILMIAH MANAJEMEN & BISNIS, 2025)
Purpose – This research aims to analyze the factors influencing the intention to adopt fintech among the public in Surabaya, using a study of the e-payment fintech Gopay, with digital literacy, risk tolerance, social influence, and performance expectancy as variables.Methodology – The research method used in this study is quantitative, and primary data was obtained thru questionnaires using Google Forms. The sample used in this study consisted of 40 respondents. Data analysis was performed using SmartPLS4 software.Findings – The analysis results indicate that digital literacy, risk tolerance, social influence, and performance expectancy significantly influence the intention to adopt fintech among the people of Surabaya. Originality/Novelty – This research develops a model by making digital literacy, risk tolerance, social influence, and performance expectancy variables that influence the intention to adopt fintech. The uniqueness of this research lies in the selection of the e-payment study of Gopay, which has digital literacy access, and the respondents are more focused on the people of Surabaya, Indonesia. Implications – Based on this research, digital literacy, risk tolerance, social influence, and performance expectancy are factors that influence and drive the intention to adopt fintech among the people of Surabaya. Therefore, stakeholders such as fintech developers, the government, and financial institutions need to consider these factors in their education and marketing strategies to optimize the penetration of fintech services.